He Role of Marketing Strategies on Local and International Students' Enrollment: A Case of Five Private Universities in Istanbul City - PATMAN, MOHAMMAD PASOON (İstanbul Kültür Üniversitesi, 2023)
Education has become a global service, and every country is attempting to give it to its population as a tool for socioeconomic growth. Educational institutes generate profitable focuses and find unique ways and preferences that satisfy the demands of students and parents as part of private sector involvement. The purpose of this study is to examine how marketing tactics affect student enrollments at Istanbul's five private universities. The study assists the administration of the various colleges in identifying the most effective marketing plans to entice more students to the institution. Marketing strategies i.e. Word of Mouth, and Advertisements (Newspaper, University Website, and Facebook) are tested in relation to Student Enrolment. Datawerecollected in hard form and as well as soft form through Google Form using simple random sampling from5 private universities functioning in Istanbul, Turkey. 390 respondents answered the questionnaire.The research results showed a significant relationship between the constructs under investigation and showed a positive relationship among all variables.
Yerli Ve Uluslararası Öğrenci Kayıtlarında Pazarlama Stratejilerinin Rolü: İstanbul'daki Beş Özel Üniversite Örneği
▪ Yüksek lisans tezi.
Keywords: Word of Mouth; Newspaper Advertisement; Student Enrollment; Facebook Advertisement; and University Website Advertisemen